2010
DOI: 10.1002/app.30960
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical properties of oil palm microfibril‐reinforced natural rubber composites

Abstract: ABSTRACT:The dynamic mechanical properties of macro and microfibers of oil palm-reinforced natural rubber (NR) composites were investigated as a function of fiber content, temperature, treatment, and frequency. By the incorporation of macrofiber to NR, the storage modulus (E') value increases while the damping factor (tan d) shifts toward higher temperature region. As the fiber content increases the damping nature of the composite decreases because of the increased stiffness imparted by the natural fibers. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 44 publications
2
41
0
1
Order By: Relevance
“…Figure ii shows that Run 1 has a higher M n value and lower tan δ, in contrast with Runs 4–6 with lower molecular mass and higher tan δ. This behaviour is explained in terms of the mobility of shorter chains that produce a higher viscous component and hence a higher flow . The damping factor of natural rubber was lower than the polymyrcene damping factors, whereas high‐ cis polybutadiene has the lowest damping factor.…”
Section: Resultsmentioning
confidence: 99%
“…Figure ii shows that Run 1 has a higher M n value and lower tan δ, in contrast with Runs 4–6 with lower molecular mass and higher tan δ. This behaviour is explained in terms of the mobility of shorter chains that produce a higher viscous component and hence a higher flow . The damping factor of natural rubber was lower than the polymyrcene damping factors, whereas high‐ cis polybutadiene has the lowest damping factor.…”
Section: Resultsmentioning
confidence: 99%
“…The storage modulus (E ), loss modulus (E"), and tan delta curves of the pristine epoxy and epoxy nanocomposites are shown in Figure 12, and the obtained DMA parameters data are summarized in Tables 6 and 7. The ability of the material to store or return energy is represented by E and provides valuable insight on the load bearing capacity [46], stiffness [23], degree of crosslinking [47], and fiber/matrix interfacial bonding [48]. The E decreases as the temperature increases with a steep change in modulus was observed in the temperature range of 60-90 • C. This can be denoted as the glass transition (T g ) region or α relaxation of the polymer whereby it represents the movement of the polymer main chain.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…Zheng et al experimented on sisal microfibril/gelatin biomass composites and reported increased tensile strength and decreased degradation ratio with increase in sisal fibril content. Joseph et al studied the dynamic mechanical properties of oil palm microfibril reinforced natural rubber composites and improved properties were observed for microfibril reinforced properties than that of macrofiber reinforced composites.…”
Section: Introductionmentioning
confidence: 99%